SPE International Symposium on Oilfield Chemistry 2013
DOI: 10.2118/164102-ms
|View full text |Cite
|
Sign up to set email alerts
|

Rock/Fluid Chemistry Impacts on Shale Fracture Behavior

Abstract: At realistic surfactant concentrations used in fracturing fluid additives, the differences in the average strengths of shale exposed to solutions of these additives are not sufficient to establish a direct correlation between the chemical effect of the surfactants and the mechanical strength of the formation. Prior studies of formations with high quartz content suggest that the adsorption of surfactant on the surface alters formation strength. In this study, using Mancos shale samples, the rock mineralogy, tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Salt helps to decrease the ionic nature of clay and thus leaves fewer sites remaining for the polymer to adsorb (Menon and Wasan 1987a;Kulshrestha et al 2004). In previous work, it has been shown that salts such as KCl minimize clay hydration and swelling, thereby minimizing the interaction of shale with fluid (van Oort 1994;Patel et al 2001;van Anderson et al 2010;Lane and Aderibigbe 2013). However, with Pride Mountain shale, the zeta potential values are higher in the presence of TMAC.…”
Section: Characterizing Polymer-shale Interaction Through Zeta Potentmentioning
confidence: 99%
“…Salt helps to decrease the ionic nature of clay and thus leaves fewer sites remaining for the polymer to adsorb (Menon and Wasan 1987a;Kulshrestha et al 2004). In previous work, it has been shown that salts such as KCl minimize clay hydration and swelling, thereby minimizing the interaction of shale with fluid (van Oort 1994;Patel et al 2001;van Anderson et al 2010;Lane and Aderibigbe 2013). However, with Pride Mountain shale, the zeta potential values are higher in the presence of TMAC.…”
Section: Characterizing Polymer-shale Interaction Through Zeta Potentmentioning
confidence: 99%
“…Hitherto, there still lack of data regarding the impact of hydrogen on subcritical crack growth. However, previous experience and knowledge from Earth's crust deformation [213,221], hydrocarbons exploitation [222][223][224], CO2 geosequestration [225] and mechanical weathering and rock erosion [226][227][228] can help to assess the impact of subcritical crack growth within fractures and reservoirs when hydrogen is involved.…”
Section: Surface Energy Change and Subcritical Crack Growthmentioning
confidence: 99%
“…Commonly, large volumes of water-based fracturing fluids are injected into the reservoir during the fracturing process. However, there is a large difference between the volume of slick water injected and flowback, which means a lot of slick water remains trapped in the reservoir and will react with the shale matrix [14][15][16]. The interaction between slick water and shale may have a great impact on the storage and flow of shale gas [15,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the wettability of shale is also critical to shale gas production, which is related to the imbibition of fracturing fluid and the possible water blocking effect, which has an important effect on the fluid transport process [16,27]. Prior researches have been done on the reaction principles of slick water and shale matrix, and it was found that the swelling of clay minerals and dissolution of carbonate minerals cause changes in pore structures of shale reservoirs [14,23,24]. Understanding how slick water changes pore structure and physical properties is essential for the design and application of fracturing [26], and the effects of slick water-shale interaction on pore structure and physical properties need further discussion [28].…”
Section: Introductionmentioning
confidence: 99%